Eastern Caribbean Currency Union : 2021 Discussion on Common Policies of Member Countries-Press Release; Staff Report; and Statement by the Executive Director for the Eastern Caribbean Currency Union. (IMF Staff Country Reports; Country Report, 2021)
The fallout from the COVID-19 crisis is hitting ECCU economies hard. Tourism receipts (accounting for nearly 40 percent of GDP) have dried up, as tourist arrivals have come to a grinding halt. The authorities successfully contained the spread of the virus at the onset of the pandemic by largely closing the borders, but a reopening of the economies since the summer has led to a surge in COVID cases. The ECCU economy is projected to contract by 16 percent in 2020 and by a further near 1\2 percent in 2021. Fiscal positions have deteriorated sharply, and public debt is projected to reach near 90 percent of GDP in 2021 and remain at an elevated level for years to come. Headline indicators suggest the financial system is relatively sound with ample liquidity buffers, but nonperforming loans are expected to rise significantly. The outlook is clouded by exceptionally high risks, including from the uncertainty concerning the evolution of the pandemic.